The role of government policies in promoting green marketing: a bibliometric review - Jamal, Adrian Arya Nugraha; Handayani , Siti Dyah; Ahmad , Jamaluddin (Department of Government Studies, Universitas Muhammadiyah Makassar, 2025)
This study aims to map the development and relationship between green marketing, public policy, and the Role of government in supporting sustainable marketing practices globally, while identifying gaps and variations in policy effectiveness across countries. Using a bibliometric approach based on Scopus data for 2014-2024, this study analyzes publication trends, researcher collaboration patterns, keyword networks, and policy comparisons across countries. The analysis shows a significant increase in academic interest in this topic since 2021, with publication peaks in 2022 and 2023. China and India dominate research contributions, driven by proactive subsidy policies and fiscal incentives. The keyword network visualization reveals four main clusters: business and sustainability research, consumer behavior, the Role of government, and industrial strategy. Findings highlight the critical Role of policies such as subsidies, ecological labeling, and educational campaigns in increasing the adoption of green marketing and encouraging environmentally friendly consumer behavior. However, challenges still arise in the form of low consumer awareness, technological limitations, and the risk of greenwashing. The overall interpretation concludes that the integration of supportive public policies, industry readiness, consumer acceptance, and the importance of customizing strategies to the local context primarily determines the success of green marketing. This research recommends strengthening subsidy policies, education campaigns, and transparent labeling, and supports cross-sector collaboration to accelerate the transition to sustainable business practices globally.